Geografia quantitativa, por quê não? - da Silva, Bruno Claytton Oliveira; Nóbrega, Ranyére Silva (Revista Vozes dos Vales: Publicações Acadêmicas, 2018)
Historically, quantitative geography has been the target of a series of severe criticisms, mainly, its technical-methodological aspects. Nevertheless, in the current conjuncture, both global and local, it is believed that several are the signs that point to a reemergence of this geographical current. Given this scenario, the article is about a new perception about Quantitative Geography, which is understood to be fully underway. Thus, it was initially aimed at analyzing the historical process of epistemological clash - among the various currents of geographic thought - in the light of its methodological approaches. Subsequently, it was desired to re-signify the historical position of Quantitative Geography in geographic science; in addition to presenting possibilities for their employment in the present day. For this purpose, several bibliographic literary resources were used. In addition, it should be noted that the type of research carried out, according to the criteria Nature, Approach, Objectives and Technical Procedures, was classified, respectively, as Basic, Qualitative, Exploratory and Bibliographic. Among the results, it was noticed that for the use of the techniques inherent to Quantitative Geography, the geographers demanded a dedication beyond the one that, historically, had been realized. Therefore, such needs justified, at least partially, the historical process of refutation of the said chain. At the same time, it recognizes that, in view of its applications and specific technical and methodological aspects, several of the aforementioned criticisms of Quantitative Geography are plausible. It was concluded that Quantitative Geography, as well as its methods, techniques, analytical and technological instruments, has an important role in the understanding of the complex dynamics of the existing spatial interrelations, notable in diverse spatio-temporal scales.